Performance Evaluation of the Regional Aids Commission in New Case Detection Rate Activities - Astuti, Rita; Saimi, Saimi; Sastrawan, Sastrawan (IKIP Mataram, 2024)
HIV/AIDS remains a significant public health concern in Indonesia, with reported cases reaching 519,158 in 2022, including 1,188 children. The Indonesian government prioritizes HIV/AIDS control within its Minimum Service Standards, yet effective implementation varies by region. This study evaluates the performance of the Regional AIDS Control Commission (KPAD) in Bima City, focusing on their role in detecting new HIV cases. Using a qualitative design, data were gathered through interviews with seven key informants, providing insights into KPAD’s operational and strategic challenges. Findings indicate that while Bima City KPAD holds primary responsibility for HIV/AIDS control, its impact has been limited. Operational setbacks, such as inadequate coordination with health services and restricted funding, have hindered effective case detection and public health outreach. By the end of 2022, Bima City recorded 31 new HIV cases, yet KPAD's involvement in early detection and case management remains suboptimal. Despite well-formulated plans within technical units, KPAD lacks proactive engagement, impeding its ability to fulfill its role as the leading agency for HIV/AIDS control. The study highlights the need for enhanced coordination, clearer role delineation, and robust advocacy to strengthen KPAD’s effectiveness. Greater collaboration across health services and community organizations could amplify early detection efforts and improve treatment adherence, ultimately supporting Indonesia’s HIV/AIDS control objectives. This research underscores the critical role of inter-agency synergy in advancing HIV/AIDS prevention and management in Bima City.